HEIRS OF DIFFERENT RELIGIONS FROM THE PERSPECTIVE OF YŪSUF AL-QARḌĀWĪ AND WAHBAH AL-ZUḤAILĪ - Asman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research discusses the views of contemporary scholars, namely Yūsuf al-Qarḍāwī and Wahbah Al-Zuḥailī have their own provisions in the inheritance law of different religions. The provisions of the law of inheritance of different religions according to Yūsuf al-Qarḍāwī are, first, allowing Muslims to inherit property from disbelievers dhimmī. Second, a person who converts to Islam before the distribution of inheritance is still entitled to receive inheritance. Third, because of trust, a person who frees his pagan slave is entitled to receive an inheritance. Meanwhile, the provisions of the law of inheritance of different religions according to Wahbah Al-Zuḥailī are prohibited for muslims to inherit property from non-Muslims (kafirs) absolutely for any reason, because it is to protect walayah from being cut off between muslims and non-Muslims. The focus of this study is how yūsuf al-qarḍāwī and Wahbah al-zuḥailī view the inheritance of different religions. Meanwhile, the method in this study is to use a literature approach. As a result of this study, Yūsuf al-Qarḍāwī forbade inheritance of different religions if the inheritance is given to the infidels of the ḥarbi. Wahbah al-Zuḥailī agrees with the hadith of the Prophet (saw), about the permissibility of non-Muslims to inherit Muslims, and vice versa, and as a form of reciting muṭlaq. Because the word